Physical properties of natural dyes based on lawsonia inermis, azadiractha indica and curcuma longa coated with superhydrphobic coating for textile applications - Thana Singam, Rupashinii; Marsi, Noraini; Mamat, Hasri; Mohd Rus, Anika Zafiah; Nasir, Siti Hana; Shaari, Muhammad Farid (IAEME Publication, 2020)
Natural dyes based on Lawsonia Inermis, Azadiractha Indica and Curcuma Longa were used in this study to produce eco-friendly and non-toxic fabric to the people. The extraction process of natural dyes is aqueous technique and hot bath dyeing. The aim is to find the optimum concentration of natural dyes and superhydrophobic coating oncotton fabric for green technology dyeing. The data obtained is subjected to quantitativeanalysis. It is found that coated fabrics have higher physical strength than uncoatedfabrics. The coated scale for crocking test, weather resistance of fabric and washingtest are 5 (excellent) compared to the uncoated dyed cotton fabric. The optimumconcentration obtained from Lawsonia Inermis, Azadiractha Indica and CurcumaLonga is F (1.50 g/ml). The results can help to reduce the usage of synthetic dye intextile application.